Reclaiming America : Nike, clean air, and the new national activism - Shaw, Randy, 1956- (University of California Press, 1999)
Have activists taken the bumper-sticker adage ""Think Globally, Act Locally"" too literally? Randy Shaw argues that they have, with destructive consequences for America. Since the 1970s, activist participation in national struggles has steadily given way to a nearly exclusive focus on local issues. America's political and corporate elite has succeeded in controlling the national agenda, while their adversaries--the citizen activists and organizations who spent.